Rating model of logistic attractiveness on the example of the Russian Federation - Kuznetsova, Anastasia A.; Burtseva, Tatiana A.; Osipova, Tatiana A.; Grankov, Pavel Yu. (The journal of contemporary issues in business and government, 2021)
The purpose of the work is to determine objective criteria that can serve as the basis for complementing state statistics systems to assess the full potential of the logistics services market. Countries and world statistical systems have to highlight new competitive advantages of territories, regions, and states. Applying a systematic approach, economical methods for processing special data, and an analysis of data arrays we obtained a system of statistical indicators comprising five elemental databases, that allowed to assess logistics attractiveness of the subjects of the Central Federal District of the Russian Federation and Russia’s logistics attractiveness relative to some other countries. The developed rating complements and refines the existing methods for assessing the investment attractiveness of regions. Evaluating the data to formulate the logistic attractiveness rating reveals additional competitive factors for certain territories, since the developed rating technique outlines the quantitative boundaries of the parameters of the created logistics infrastructure.